Healthcare Utilization by Frail, Community-Dwelling Older Veterans: A 1-Year Follow-up Study. Issue 11 (November 2017) - Zylberglait Lisigurski, Miriam; Bueno, Yolin A.; Karanam, Chandana; Andrade, Allen D.; Akkineni, Sisir; Cevallos, Victor; Ruiz, Jorge G.
Abstract : Objectives: Frailty is a prevalent clinical syndrome associated with a high risk of adverse health outcomes, including disability, morbidity, and mortality, that has become a major challenge for the healthcare system. The aim of this prospective study was to determine the level of healthcare utilization in prefrail and frail community-dwelling older military veterans. Methods: We studied a cohort of community-dwelling older veterans aged 65 years and older 1 year at the Miami Veterans Affairs Medical Center to determine their levels of healthcare utilization. We administered the 5-item FRAIL (Fatigue, Resistance, Ambulation, Illnesses, & Loss of Weight) scale, from which patients were categorized into three groups: robust, prefrail, and frail. Chart reviews were conducted to confirm weight loss and number of illnesses. One year later, information regarding hospital admissions, emergency department (ED) visits, and primary care visits was obtained. Results: We evaluated 291 participants, mean age 74 ± 8 years, 112 (38.5%) of whom were African American, 179 (61.5%) were white, and 40 (13.7%) were Hispanic. Overall, 49 (16.8%) participants were frail, and 161 (55.4%) prefrail. After adjusting for age and Charlson Comorbidity Index, frail status was associated with ED admission (odds ratio [OR] 2.7, 95% confidence interval [CI] 1.2–6.1) and primary care visits (OR 3.4, 95% CI 1.5–7.3); however, it was not significantly associated with hospital admission (OR 2.2, 95% CI 0.9–5.2). Conclusions: In a sample of community-dwelling older veterans, frailty was found to be significantly associated with an increased frequency of ED visits and primary care visits, but not with hospital admissions. Identifying patients with frailty may allow for targeted interventions that improve healthcare outcomes and may reduce healthcare utilization. Abstract : Frailty is a clinical syndrome that affects older adults and is associated with a high risk of adverse health outcomes, including disability, morbidity, and mortality. The aim of this study was to determine the level of healthcare utilization in frail, community-dwelling older military veterans. This prospective study demonstrated that frailty was significantly associated with an increased frequency of emergency department visits and primary care visits in communitydwelling older veterans. Identifying patients with frailty may allow for targeted interventions that improve healthcare outcomes and potentially reduce healthcare utilization